In vitro bioactive properties of intact and enzymatically hydrolysed whey protein: targeting the enteroinsular axis. Issue 3 (11th March 2015) - Power-Grant, O.; Bruen, C.; Brennan, L.; Giblin, L.; Jakeman, P.; FitzGerald, R. J.
<x xml:space="preserve">Abstract</x> This work identified extensively hydrolysed whey protein hydrolysates with multifunctional (insulinotropic, dipeptidyl peptidase IV inhibitory and antioxidative) bioactive properties.